2021
DOI: 10.1007/s42114-021-00332-y
|View full text |Cite
|
Sign up to set email alerts
|

Electrically conductive polymer composite containing hybrid graphene nanoplatelets and carbon nanotubes: synergistic effect and tunable conductivity anisotropy

Abstract: Pristine carbon nanotubes (CNTs) and functionalized carbon nanotubes (f-CNTs) were introduced into conductive poly(methyl methacrylate)/graphene nanoplatelet (PMMA/GNP) composites to achieve a synergistic effect in the enhancement of the conductivity and the reduction in the percolation threshold by forming a 3-Dimensional(3-D) hybrid structure. Both the in-plane and perpendicular electrical properties were investigated. The synergies of hybrid fillers in the in-plane direction were more dependent on the total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 63 publications
(68 reference statements)
0
39
0
Order By: Relevance
“…Moreover, the addition of magnetic nanoparticles to composites with carbon nanoinclusions can cause additional electromagnetic shielding due to magnetic losses [ 13 ]. For composites with several nanoparticle types, the synergy effect becomes important, which is the enhancement of composite properties due to interactions of nanoparticles inside the polymer matrix [ 14 , 15 ]. For example, in hybrid composites, the percolation threshold can be substantially lower, while electromagnetic properties are significantly better than in composites with one type inclusions [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the addition of magnetic nanoparticles to composites with carbon nanoinclusions can cause additional electromagnetic shielding due to magnetic losses [ 13 ]. For composites with several nanoparticle types, the synergy effect becomes important, which is the enhancement of composite properties due to interactions of nanoparticles inside the polymer matrix [ 14 , 15 ]. For example, in hybrid composites, the percolation threshold can be substantially lower, while electromagnetic properties are significantly better than in composites with one type inclusions [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Investigations on the replenishment mechanism of the electrolyte and additives as well as economic estimations of the cost input and output return for crude Pb electrorefining in the Lugalvan BNO12-assisted MSA system are now being performed. The energetic performance and process design of electrorefining would be further improved by low-investment microkinetic modeling. Preparation of novel electrodes with nano- and polymeric materials will further improve the electrochemical performance of the deposition process. The continuous drop in price of renewable electricity would further advance electrorefining toward lower-cost operation. Overall, crude Pb electrorefining in the Lugalvan BNO12-assisted MSA system would operate in a more technically and economically beneficial mode once receiving reasonable optimizations of process and condition and hold great potential toward practical application.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the synergy of secondary filler with the primary one through the creation of a more developed filler network structure contributes to the reinforcement of polymer matrixes. It was shown that hybrid filler systems can improve the dispersion state, [8][9][10][11][12] the mechanical, [8,[11][12][13] dynamic, [10,12,14,15] tribological, [10,12,15,16] and also thermal, [17] electrical [18] and electromagnetic wave absorption [19] performance of polymer composites. The driving force behind the formation of a hybrid network and its synergy on the final performance of composites has been the subject of numerous studies in the literature.…”
Section: Introductionmentioning
confidence: 99%